The Analysis on Space Radiation Environment and Effect of the KOMPSAT-2 Spacecraft(II): Single Event Effect - Myung-Jin Baek; Day-Young Kim; Hak-Jung Kim (Journal of Astronomy and Space Sciences, 2001)
In this paper, space radiation environment and single event effect(SEE) have been analyzed for the KOMPSAT-2 operational orbit. As spacecraft external and internal space environment, trapped proton, SEP(solar energetic particle) and GCR(galactic cosmic ray) high energy protons and heavy ions spectrums are analyzed. Finally, SEU and SEL rate prediction has been perfomed for the Intel 80386 microprocessor CPU that is planned to be used in the KOMPSAT-2. As the estimation results, under nominal operational condition, it is predicted that trapped proton and high energetic proton induced SEU effect will not occur. But, it is predicted that heavy ion induced SEU can occur several times during KOMPSAT-2 3-year mission operation. KOMPSAT-2 has been implementing system level design to mitigate SEU occurrence using processor CPU error detection function of the on-board flight software.